Assessment of work ability in competing strands of social insurance: the German case. (26th June 2017) - Aurich-Beerheide, Patrizia; Brussig, Martin
Abstract : The article describes the system of social security in the case of incapacity in Germany and analyses how the pathway into incapacity benefits is structured. A special focus of the article is on conditionality as it is applied in different systems of social security in Germany today. A main result of the analysis is that incapacity benefits are embedded into a chain of different benefits and social services for persons with limited work ability. For the German case, this leads to a defensive reaction from both the Public Employment Service and pension insurers.